93.1k views
0 votes
The function h ( x ) = 1 x − 1 h ( x ) = 1 x - 1 can be expressed in the form f ( g ( x ) ) f ( g ( x ) ) , where g ( x ) = ( x − 1 ) g ( x ) = ( x - 1 ) , and f ( x ) f ( x ) is defined as:

User Jenette
by
5.5k points

1 Answer

4 votes

Answer: f(x) = 1^(x + 1)

Explanation:

we have that h(x) = 1^x

and h(x) = f(g(x))

This mean that we are evaluating the function f(y) in the point y = g(x)

where g(x) = x - 1

then:

f(g(x) = f(x - 1) = h(x) = 1^x

then we should have that:

f(x) = 1^(x + 1)

then:

f(x - 1) = 1^(x - 1 + 1) = 1^x

User Andrei Chevozerov
by
6.8k points